Cu, Zn Superoxide Dismutase from Radix Lethospermi seed: Purification and Characterization - Haddad, Namir; Yuan, Qinsheng (Iraqi Journal of Science, 2025)
The Cu, ZnSOD was purified from Radis lethospermi seed by ammonium sulphate precipitation followed by column chromatography using DEAE-FF, Sephadex G- 100and hydroxylapatite chromatography. Before extraction lipid was renoved by super critical fluid extraction (SCF). Pure copper, zinc superoxide dismutase bad a specific activity of 3555.9 units per milligram protein and was purified 211.5-fold with a yield of 19.3%. The isozyme has a molecular weight of 33 KDa and is composed of two non-covalently joined equal subunits, having 0.9340.02 g.atom Cu and 0.79-0.01 gatom Zn for each. The purified enzyme was stable over a pil range of 6.0-9.0 at 25°C and a temperature range of 25-45 °C. The purified RLS Cu,ZaSOD was sensitive to both cyanide and hydrogen peroxide which is typical of CuZn SODs but was not inhibited by DTT, NaN, and B-mercaptoethanol